Assessing the Impact of Public Policy on Homicide Rates in Brazil: The Case of PRONASCI Program. (December 2021) - de Castro, Talita Egevardt; Justus, Marcelo; Kassouf, Ana Lúcia
The current study evaluates the impact of the National Public Security with Citizenship Program (PRONASCI) on the homicide rate in Brazilian municipalities. PRONASCI program was implemented in Brazilian metropolitan regions and urban territories with high violent crime rates in 2007. In this study, we have applied a spatial difference-in-differences model with matching approaches. Municipalities that did not receive funds from the program made up the control group. We found that the program was inefficient to reduce the homicide rate in all of the municipalities that had received funds from it, compared to those that had not, even considering their potential spatial spillover effects. This result was expected due to the program complexity, in particular due to its ineffective management and the resistance from municipalities to change with the program.